2023 THE ROLE OF PARENTS IN THE FORMATION OF SPIRITUAL AND AESTHETIC QUALITIES OF PRESCHOOL CHILDREN WHEN TEACHING THEM DRAWING SKILLS (E Global Congress, 2025)
The article reveals the role of parents in the spiritual and aesthetic education of their children in one of the types of visual activity - drawing. The qualities that are formed in this process are described - the aesthetic qualities and feelings of preschool children.